Optical Properties of Malachite Green Dye Doped SiO2 Glasses: Effect of Transition Metal (Fe-I) Used as a Codopant - Dulen Bora; Subrata Hazarika (International Journal of Optics)
Enhanced luminescence properties of Malachite Green (MG) (oxalate) in Fe-MG codoped SiO2 glasses compared to its values in MG doped SiO2 glasses are reported here. The enhancement is chiefly attributed to a resonance nonradiative energy transfer between Fe and MG. The quantum yield of Malachite Green (MG), in presence of Iron, trapped in sol-gel derived SiO2 glass increases by an order of ~103 compared to that in low viscous solvent while a lifetime of 3.29 ns is reported.